Development of the Bali Sari Mobile Application Prototype: Strengthening Resilience Based on Local Characteristics and Culture - Dewa Gede Firstia Wirabrata; Dewa Bagus Sanjaya; I Gede Wahyu Suwela Antara (Lembaga Bale Literasi, 2025)
This study presents the development of a prototype mobile application named Bali Sari: Strengthening Resilience Based on the Characteristics of Balinese Society. The application is designed as a culturally grounded digital innovation to support communities, particularly Balinese society, in strengthening psychological resilience and preventing mental health problems such as stress, depression, and suicide, which have become serious concerns in Bali in recent years. The Bali Sari mobile application integrates Balinese philosophy, values, and cultural practices into a digital platform that is accessible, practical, and relevant to users’ daily lives. Although the application is rooted in Balinese culture, the values embedded in it are universal and may be accepted by broader communities. For instance, Pranayama breathing techniques promote focus and relaxation, while the concept of menyama braya reflects togetherness, mutual assistance, and social solidarity, which are values shared by many societies worldwide. Therefore, the potential users of this application are not limited to Balinese communities but may also include national and international users interested in culturally based approaches to resilience and mental well-being. The Bali Sari application also has strong commercial potential because its digital and paperless format allows it to be distributed through various online platforms and accessed widely. Its main advantages include providing resilience-strengthening interventions that are more effective for Balinese people because they are adapted to local characteristics, philosophy, values, and culture, while also enabling large-scale mental health promotion. This project focuses on developing and testing the prototype to ensure its feasibility, usability, and effectiveness before wider implementation. Overall, Bali Sari is expected to contribute to the advancement of culturally responsive digital mental health interventions and serve as a model for developing similar applications for other communities.